Fundamentals Of Business Communication- AF173- 202202 - Haro Merino, Ruth Milagros (2022)
Fundamentals of Business Communication offers you the fundamentals of professional development and the tools necessary to gain employment. You crafted resumes, cover letters, and learned to research businesses and industries. In the course we take you inside the organization as a working professional and develop the skills to produce workplace ready documents. Business professionals spend 70% of their time communicating. According to NACE's Job Outlook 2015 survey, the top three skills employers seek are the abilities to lead effectively, work collaboratively, and write cogently. Employers, chief criteria for promotion are communication skills. Your ability to communicate effectively will set you apart from your peers and broaden your leadership potential. Focusing on internal messaging in the workplace, this course introduces the fundamentals of written business communication strategies.